Destination image: A review from 2012 to 2023 - Zuo Wang; Piyachat Udomwong; Jing Fu; Pintusorn Onpium (Cogent Social Sciences, 2023)
More than 50 years have passed since the first article on destination image was published, and this body of research is still one of the most popular topics in tourism studies. However, limited research has focused on recent advancements and emerging trends in destination image research. Therefore, there is a pressing need for a comprehensive and up-to-date review to evaluate its progress, identify key features, and explore future research possibilities. Employing a meta-analysis methodology, this study scrutinized 178 articles from 11 esteemed academic journals published between January 2012 and April 2023. The analysis encompasses various aspects, including the publication trends, journal distribution, productive authors, research topics and research methods. Furthermore, this study introduces the concept of “e-WOM image,” which offers a profound understanding of the intricate associations among various topics within the domain of destination image research. The exploration of “e-WOM image” as a potential research field holds promise for advancing the field of destination image research in the coming years.